Public disclosure punishment (Tasyhir) between the views of Islamic law and civil law - Husni, Ahmad Muhammad (Zes Rokman Resources (2131022-P), 2024)
Takzir punishment is not limited because it depends on the maslahah, even the government, legislature, or judge can impose any law provided it is commensurate with the offense and complies with the general maslahah. One of the types of takzir punishment imposed is the general declaration (al-Tasyhir) which is to make a public declaration of the offense of criminals so that criminals feel ashamed and depressed. This article aims to address the questions that arise on the issue of the problem of public declaration crime between the views of the law and how to overcome the present. The question that arises is how the crime of tasyhir is carried out. Apart from that, the second question raised is what the view is according to the law in Malaysia related to such crimes and the third question is what the implications of the occurrence of tasyhir crime are. Also, the last question is how to overcome the crime of tasyhir that is happening nowadays according to the development of the increasingly sophisticated world. The methodology used is a qualitative study involving library study. In addition, the design used is a content analysis study. References used in this writing are books, journals, and articles. All these references help the author a lot to gather information and be included in this writing. Meanwhile, the objective to be achieved in this study is to explain in-depth related to the crime of tasyhir as well as to know the views of the law in Malaysia in the crime of tasyhir. Study the implications of the occurrence of tasyhir crime and the last is to know how to overcome the current related to it. Next, this study is to see the extent of the development of tasyhir crime, and the implications of tasyhir crime and how to overcome it.